Up-Regulation of CD146 in Schwann Cells Following Peripheral Nerve Injury Modulates Schwann Cell Function in Regeneration - Shen, Yinying; Zhu, Jun; Liu, Qianyan; Ding, Shiyan; Dun, Xinpeng; He, Jianghong (Frontiers in Cellular Neuroscience, 2021)
CD146 is cell adhesion molecule and is implicated in a variety of physiological and pathological processes. However, the involvement of CD146 in peripheral nerve regeneration has not been studied yet. Here, we examine the spatial and temporal expression pattern of CD146 in injured mouse sciatic nerve via high-throughput data analysis, RT-PCR and immunostaining. By microarray data analysis and RT-PCR validation, we show that CD146 mRNA is significantly up-regulated in the nerve bridge and in the distal nerve stump following mouse sciatic nerve transection injury. By single cell sequencing data analysis and immunostaining, we demonstrate that CD146 is up-regulated in Schwann cells and cells associated with blood vessels following mouse peripheral nerve injury. Bioinformatic analysis revealed that CD146 not only has a key role in promoting of blood vessel regeneration but also regulates cell migration. The biological function of CD146 in Schwann cells was further investigated by knockdown of CD146 in rat primary Schwann cells. Functional assessments showed that knockdown of CD146 decreases viability and proliferation of Schwann cells but increases Schwann cell migration. Collectively, our findings imply that CD146 could be a key cell adhesion molecule that is up-regulated in injured peripheral nerves to regulate peripheral nerve regeneration.